O Emprego de Minerais Pesados como Indicador da Proveniência da Cobertura Pedológica do Arenito Caiuá na Região Noroeste do Paraná - GASPARETTO, NELSON VICENTE LOVATTO; DOS SANTOS, MANOEL LUIS (Pesquisas em Geociências, 2005)
<!– .p text-align: justify; –> This paper aims the identification of the translucent heavy minerals that occur in the pedological covering at the northwestern region Paraná state (Brazil), and compare them to the minerals observed in the Caiuá sandstone that orverlies it. The origin of the pedological covering is controversial because many researches consider it to be colluvium, originated during a semi-arid climate that occurred in the Quaternary. To reach the proposed goals, morphological descriptions along the top sequences were done and samples from different profiles of the trenches were collected. A slight mineralogical diversity was observed at the pedological covering and at the Caiuá sandstone, where the main minerals are staurolite, rutile, tourmaline and zircon, followed by lower amounts of garnet, kyanite and dumortierite. This assemblage of minerals suggests a high textural and mineral maturity of the studied materials. It is an important argument concerning the origin of the pedological covering, suggesting that it was derived from the alteration processes of the overlaying sandstone, thus, confirming the residual characteristics of said materials in northwestern Paraná state.